In search of European liberalisms concepts, languages, ideologies - Freeden, Michael; Fernández Sebastián, Javier, 1952-; Leonhard, Jörn (European conceptual history ;, 2019)
"Since the Enlightenment, liberalism as a concept has been foundational for European identity and politics, even as it has been increasingly interrogated and contested. This comprehensive study takes a fresh look at the diverse understandings and interpretations of the idea of liberalism in Europe, encompassing not just the familiar movements, doctrines, and political parties that fall under the heading of "liberal" but also the intertwined historical currents of thought behind them. Here we find not an abstract, universalized liberalism, but a complex and overlapping configuration of liberalisms tied to diverse linguistic, temporal, and political contexts"--